Contemporary management and prognosis of great vessels trauma. Issue 6 (June 2019) - Chen, Szu-An; Huang, Jen-Fu; Tee, Yu-San; Chen, Shao-Wei; Wang, Shang-Yu; Fu, Chih-Yuan; Hsieh, Chi-Hsun; Liao, Chien-Hung
Highlights: Great vessel trauma is rare but highly lethal in clinical practice. Patient survival depends on injury severity, the grade of shock status and injury site. The prognosis of aortic trauma seemed promising with the advent of endovascular treatment. The outcomes with vena caval injuries are still disappointing and need different levels of surgical expertise and novel treatment methods to improve the clinical outcomes. Abstract: Background: Great vessel trauma (GVT), which is defined as trauma to the aorta or vena cava, remains one of the most challenging injuries to treat and has a high mortality rate despite advances in modern medicine. Additionally, the optimal management of GVT is controversial. In this study, we review the incidence, management, and outcome of GVT, identify the current status and prognostic factors of GVT, and compare treatment outcomes. Methods: We conducted a retrospective, single-center, cohort study of patients with GVT in a Level I trauma center from August 2008 to December 2013. We retrieved demographic data, physical and imaging findings, injury severity score (ISS), treatment choice, length of hospital stay, and mortality. We analyzed the risks of adverse outcomes and mortality. Results: The seventy-four patients in this cohort had a mean age of 41.6 (SD 17.7) years and a high mortality rate of 27%. The prognostic factors of survival with GVT included male gender, lower ISS, higher GCS, higher SBP and DBP and vena caval injuries. We also determined that vena caval injury is the main factor that can predict mortality. Conclusion: In conclusion, GVT is relatively rare but often lethal in clinical practice. Patient survival depends on injury severity and the shock status grade. Aggressive resuscitation and treatment play important roles in survival. The coordination of different levels of surgical expertise and the application of novel treatment methods are required to improve clinical outcomes for patients with vena caval injuries.